Penilaian Pengetahuan dan Sikap terhadap Informasi tentang Merkuri yang Ditemukan dalam Produk Kosmetik dan Potensi Risikonya bagi Kesehatan - Lita Rosa (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to find out their knowledge about the mercury content which can damage health. This study used quantitative research. The data technique for our study used primary and secondary data. Researchers used categorical aggregation data analysis techniques and naturalistic generalization of case studies. The results showed that the number of ART aged 20 to 30 years with a total of 57 respondents or 73%. While the remaining 27% or as many as 21 respondents aged 31 to 40 years. Related to the respondent's level of knowledge. There are 31 ART (77.5%) who have a low level of knowledge related to cosmetics. Furthermore, respondents with high knowledge may be 9 household members (22.5%). Maid Attitudes and middle-down circles towards mermerkuri cosmetics tend to be negative. helpers and middle class and lower class who have signatures of 21 household members (52.5 percent). ART who had positive attitudes were 19 (47.5 percent). The conclusion of this study is the level of knowledge and attitudes of the relationship to information about mercury found in cosmetic products and its potential health risks. Based on the results of the study, it shows that the respondents in the survey did not seem to see the dangers of using mercury in the long term.